PSIV-39 Comparative transcriptome profile of genes differentially expressed in longissimus dorsi muscles between Japanese black (Wagyu) and Chinese Red Steppes cattle. (7th December 2018) - Fang, X; Zhao, Z; Jiang, P; Xia, L; Ge, Y; Wang, M; Li, G; Yang, R
Abstract: Significant differences in meat quality traits have been reported between Japanese black cattle (Wagyu) and Chinese Red Steppes, which presented a unique model for analyzing the effects of transcriptional level on meat quality traits. In this study, longissimus dorsi muscle samples of Wagyu and Chinese Red Steppes cattle were provided by the National Research Center for Animal Transgenic Bio-technology, Inner Mongolia University and Branch of Animal Science, Jilin Academy of Agricultural Sciences, respectively. The quality and quantity of total RNA were determined using an Agilent 2100 Bioanlyzer (Agilent technologies, Palo Alto, CA). Library concentration was quantified by quantitative qPCR and a Qubit® 2.0 Flurometer, and the cDNA libraries were sequenced using the Illumina HiSeq2000 platform by the Beijing Genomics Institute. Fluorescence quantitative PCR and western blot were used to verify the data of sequencing and bioinformatic analysis. 388 differentially expressed genes (Log2FC>0.585 or <-0.585, FDR<0.05) were found between Wagyu and Chinese Red Steppes cattle. Among them, 205 genes were higher and 183 genes were lower expressed in Wagyu than Chinese Red Steppes cattle (p<0.05). Specifically, a large number of differentially expressed genes involved in growth and lipid metabolism, such as ASIP, SDC3, CD44, ALDH9A1, EHHADH, AGRN, etc. Gene ontology (GO) analysis showed that 362 DEGs were enriched in 3071 GO terms, among which 475 GO terms were significantly enriched and KEGG analysis indicated that 138 DEGs were enriched in 171 pathways, of which 11 pathways were significantly enriched (p<0.05). The expression levels of DEGs were detected by fluorescence quantitative PCR and Western Blot which were consistent with the sequencing result. Our results identified novel candidate genes correlated with meat quality traits, which will be valuable for future functional gene studies of fat deposition and improvement of meat quality traits of beef cattle.